Pengaruh Penambahan Serbuk Batu Bata Sebagai Pengganti Sebagian Filler Pada Laston (AC-BC) Terhadap Karakteristik Marshall Dengan Variasi Perendaman - Damayanti, Alilah Saskia; Nurdin, Abdul Rahim; Setiawan, Arman (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
This research aims to determine the effect of adding brick powder filler on the properties of asphalt concrete mixture with soaking variations. This study used brick powder with variations of 0%, 10%, 15%, and 20%. The test pieces were made as many as 36 samples, for each variation as many as 3 samples. The test piece is soaked with repeated variations of soaking for 3, 7 as well as 10 days. The method used is the conventional marshall method to obtain mixed properties. The results of this test showed that each variation decreased with the addition of brick powder. in the variation of brick powder 20% the flow value has increased to exceed the specification limit of 4.14% from what has been determined by Bina Marga 2018, which is 2-4% (mm). As for the 0%, 10% and 15% variations have met the 2018 Bina Marga specifications